2021
DOI: 10.1108/oir-03-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

How electronic word of mouth (e-WOM) triggers intention to visit through destination image, trust and satisfaction: the perception of a potential tourist in Japan and Indonesia

Abstract: PurposeThe purpose of the paper is to analyze the different results between the effects of electronic word of mouth (e-WOM) on the perception of potential tourist in Japan and Indonesia regarding destination image, destination trust, satisfaction and their intention to visit.Design/methodology/approachThis research method is a structural model. Based on the existing literature review, several variables were obtained which were then analyzed by WarpPLS 6.0 software. The sampling method applied in this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…The positive association between trust and behavioural intention in tourism has been confirmed (Abubakar et al, 2017;Rasoolimanesh et al, 2021). Though studies have explored the influence of destination image on trust (Chen & Phou, 2013;Setiawan et al, 2021;Su et al, 2017), the reverse relationship remains unexplored. Individuals trust in a government's COVID-19 management actions was revealed to play a key role in implementing and accepting the implemented measure (Fancourt et al, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 94%
“…The positive association between trust and behavioural intention in tourism has been confirmed (Abubakar et al, 2017;Rasoolimanesh et al, 2021). Though studies have explored the influence of destination image on trust (Chen & Phou, 2013;Setiawan et al, 2021;Su et al, 2017), the reverse relationship remains unexplored. Individuals trust in a government's COVID-19 management actions was revealed to play a key role in implementing and accepting the implemented measure (Fancourt et al, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 94%
“…Berbagai penelitian menyebutkan bahwa e-WOM memiliki korelasi kuat dengan industri pariwisata. Misalnya pengaruh e-WOM terhadap intensi seseorang melakukan wisata kesehatan atau wisata medis (Abubakar and Ilkan, 2016), pengaruh e-WOM terhadap intensi seseorang untuk berkunjung ke destinasi wisata (Jalilvand & Samiei, 2012), peran e-WOM dalam meningkatkan jumlah kunjungan wisata ke kebun anggur (Strickland and Williams, 2022), dan e-WOM memiliki pengaruh langsung terhadap citra destinasi dan keinginan untuk berkunjung (Setiawan et al, 2021). Untuk itu, WOM dan e-WOM memainkan peran penting pada layanan yang memiliki kualitas kepercayaan tinggi seperti industri pariwisata (Jalilvand & Samiei, 2012).…”
Section: Pendahuluanunclassified
“…Previous research found that on the TripAdvisor website, online reviews and recommendations significantly impact tourists' perceptions of a destination (Abbasi et al, 2023;Marine-Roig & Huertas, 2020). This indicates that positive reviews enhance a positive image (Setiawan et al, 2021). Digital word of mouth on social media can influence destination image and visit intentions (Abbasi et al, 2023;Setiawan et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Comments and reviews from tourists significantly impact tourist expectations and decisions (Lam, Ismail, & Lee, 2020). Positive comments can increase trust and interest in visiting a tourist destination, as can negative comments (Setiawan et al, 2021). (Goyal & Taneja, 2023) state that tourists tend to trust peer reviews more than advertisements or promotions.…”
Section: Introductionmentioning
confidence: 99%